Mortalidade por causas externas no sexo feminino no Espírito Santo : estudo ecológico - Comério, Tatiane (2011)
The first objective sought to analyze the completeness of the Information System of Mortality data on the feminine’s deaths caused by external reasons in the State of Espirito Santo, Southeast area and Brazil (1998 to 2007). Descriptive, analytic, study based on secondary data. The deaths registered during the variables fill in the death certificate (DC) at that time were also included. A score was used to evaluate the level of non completeness. The model chosen equations and the adjustment statistic for the percentages of the missing data throughout the time (R value and the p-value of the F test) were taken from the SPSS program. There is a significance level of 5%. There was stability of the rates in Espirito Santo State, Southeast and Brazil for the age and occurrence place variables. In the other variables there is a significant improvement in the DC fill, however, considering schooling the non completeness percentage is still very bad for Espirito Santo. Strategy for advance of the filling quality of DC. The second objective analyzed the tendency of the feminine’s mortality caused by external reasons in the State of Espirito Santo in the period of 1980 to 2007. It is a time series study, which data is taken from the Information System of Mortality and the people’s estimate according to age and calendar year, from the Brazilian Institute of Geography and Statistics. The specific coefficients of mortality, according to age, were annually calculated. The analysis of tendency was made through the standardization of the mortality rates by the direct method, which the IBGE - 2000 census population was considered standard. In order to calculate rates, 7.0 Excel Microsoft Program was used. The equations of linear tendency and the statistics of model adjustment (R value and p- value of the F test of the model adequacy) were taken from the SPSS Program. The level of significance used was 5%. There was a decreasing tendency in the ages of 0 to 4 (61, 5%) and 5 to 9 (37, 5%) in the period when the study was held and an increasing tendency in the age of 80 years old and more in the year of 1996. Results indicate the need to implement conjunct public politics directed to the control of the violence. Investments in education are recommended aiming at the control of the fast rise of the mortality caused by external reasons, mainly among the elderly living in the state of Espirito Santo.